Graphene/GaSe-Nanosheet Hybrid: Towards High Gain and Fast Photoresponse - Lu, R. T.; Liu, J. W.; Luo, H. F.; Chikan, Viktor; Wu, J. Z. (My University, 2016)
While high photoconductive gain has been recently achieved in graphene-based hybrid phototransistors using semiconductor two-dimensional transition/post-transition metal dichalcogenides or quantum dots sensitizers, obtaining fast photoresponse simutaneously remains a challenge that must be addressed for practical applications. In this paper we report a graphene/GaSe nanosheets hybrid photodetector, in which GaSe nanosheets provide a favorable geometric link to graphene conductive layer through van Der Waals force. After a vacuum annealing process, a high gain in exceeding 107 has been obtained simitaneously with a dynamic response time of around 10 ms for both light on and off. We attribute the high performance to the elimination of possible deep charge traps, most probably at the graphene/GaSe nanosheets interface. This result demonstrates high photoconductive gain and fast photoresponse can be achieved simultaneously and a clean interface is the key to the high performance of these hybrid devices.
Citation: Lu, R. T., Liu, J. W., Luo, H. F., Chikan, V., & Wu, J. Z. (2016). Graphene/GaSe-Nanosheet Hybrid: Towards High Gain and Fast Photoresponse. Scientific Reports, 6, 7. doi:10.1038/srep19161
Keywords: Gase Nanoparticles; Relaxation Dynamics; Gallium Selenide; Quantum Dots; Photodetectors; Devices